Ligand Excess "Inverse-Defected" Zr-6 Tetrahedral Tetracarboxylate Framework and Its Thermal Transformation - Nateghi, Bahareh; Domasevitch, Kostiantyn V.; Bulánek, Roman; Janiak, Christoph; Boldog, István (American Chemical Society, 2019)
A new porous coordination polymer (PCP/MOF), ZRTE-10, based on a tetrahedral 1,3,5,7-tetra(carboxyphenyl)-benzene ligand (H4L4) was synthesized using formic or acetic acids as modulators. The low symmetry (C2/c) framework, [Zr-6(mu(3)-O)(4)(mu(3)-OH )(4)(L-4)(HL4)(2)(OH)(2)(H2O)(2)], is built upon a rare 10-connected Zr-6 cluster. Two-thirds of the ligands bear one nondeprotonated carboxy group, and the framework has a complex trinodal 3,4,10-c, {4(14).6(24).8(7)}{4(3)}(2){4(5).6}, underlying net. Supercritical CO2 drying and mild degassing at 120 degrees C yielded a porous material with S-BET = 1190 m(2) g(-1). When heated up to similar to 200 degrees C, ZRTE-10 converts to another crystalline framework, ZRTE-11. The latter was identified to be identical to the expected fluorite (flu) observed previously for other tetrahedral ligands. The high symmetry (I4/m) framework is built upon 8-connected Zr-6 clusters and has a formula of [Zr-6(mu(3)-O)(4)(mu(3)-OH )(4)(L-4)(2)]. The complicated trinodal network of ZRTE-10 and the simple flu net in ZRTE-11 are topologically interrelated via the operation of the merging of two neighbor three-connected nodes to one fourconnected one. The thermally induced conversion of ZRTE-10 proceeds with expulsion of one ligand per Zr-6 node in the pores of the framework, resulting in a relatively low S-BET = 585 m(2) g(-1) for the activated H4L4@ZRTE-11. A mixed ligand approach for ZRTE-10,11 was attempted using 1,3,5-tetra(carboxyphenyl)benzene (H3L3), which is a truncated analog of H4L4 with one missing branch. The monocrystalline sample of ZRTE-10 obtained in small yields demonstrated only minor inclusion of H3L3. However, the high-yielding (similar to 80%) procedure with HCl as a modulator allows near proportional incorporation of the ligands. The formed materials are semiamorphous with powder XRDs intermediary between pure ZRTE-10 and -11. Thermal treatment of the semiamorphous materials increases their crystallinity and allows S-BET = 400-550 m(2) g(-1) surface areas to be reached for pure H4L4 and H3L3 or their mixture alike. The approach proposes a viewpoint on the H3L3 trifunctional ligand as a model of a ligand platform, suitable for bearing a large functionality on the fourth "truncated" branch. The significance of ZRTE-10 as a material for postsynthetic introduction of metal-based cluster functionality and as a model of functionality encapsulation, an alternative to the ship-in-the-bottle method, is discussed.
Přebytek ligandů v inverzně defektní Zr6 tetraedrálně tetrakarboxylové mřížce a její tepelná transfromace
Keywords: metal-organic frameworks; high-performance; uio-66; design; adsorption; truncation; geometry; sorption; mofs; tool; metal-organická mřížka; uio-66; adsorpce; geometrie; sorpce; MOFs